Handbook of High‐resolution Spectroscopy 2011
DOI: 10.1002/9780470749593.hrs060
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Jahn–Teller Effect

Abstract: An overview of theoretical treatments of Jahn–Teller (JT) and pseudo‐Jahn–Teller (PJT) coupling effects involving doubly degenerate electronic states is presented. It is divided into a general part, focusing on the pertinent Hamiltonians and the properties of the adiabatic potential energy surfaces, and the presentation of specific examples, where the consequences for molecular electronic spectra are demonstrated. Besides isolated E electronic states with various types and symmetries of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 113 publications
0
14
0
1
Order By: Relevance
“…Our formal proposal is that unless the vibrational profiles of two or more transitions into electronic ionic states are not separate in the PES, then vibronic coupling should be assumed. [48][49][50] Measured vibrational separations will at best be perturbed values and are not directly comparable with the harmonic wavenumbers derived from theoretical equilibrium structures. As an indicator, a gap in the PES should occur, where the baseline is re-established, before a succeeding state is regarded as unperturbed.…”
Section: Discussionmentioning
confidence: 99%
“…Our formal proposal is that unless the vibrational profiles of two or more transitions into electronic ionic states are not separate in the PES, then vibronic coupling should be assumed. [48][49][50] Measured vibrational separations will at best be perturbed values and are not directly comparable with the harmonic wavenumbers derived from theoretical equilibrium structures. As an indicator, a gap in the PES should occur, where the baseline is re-established, before a succeeding state is regarded as unperturbed.…”
Section: Discussionmentioning
confidence: 99%
“…This has made the rotation-vibration spectra of much more complex molecules accessible to the full analysis of the rotational-vibrational fine structure and the frontier in this area of research is moving toward even larger polyatomic molecules. Several articles in this handbook discuss these experimental developments (see, for instance, : High-resolution Fourier Transform Infrared Spectroscopy, Snels et al 2011 In parallel to the experimental developments, there has been great progress in the theoretical understanding of the quantum mechanics of molecules on the basis of quantum chemical ab initio theory as well as quantum dynamics in general (see Yamaguchi and Boudon et al 2011: Spherical Top Theory and Molecular Spectra, Köppel et al 2011: Theory of the Jahn-Teller Effect and Field et al 2011: Effective Hamiltonians for Electronic Fine Structure and Polyatomic Vibrations, this handbook). Thus, many aspects of rotation-vibration spectroscopy are covered in great detail in the individual articles of this handbook.…”
Section: Introductionmentioning
confidence: 99%
“…Special cases characterized by a high molecular symmetry, such as the "Renner-Teller" and "Jahn-Teller (JT) effects" are particularly interesting because they enable one to study the vibronic interactions in detail, thanks to symmetry selection rules. Comprehensive theories of vibronic coupling have been formulated (see Köppel et al 2011: angular momentum about the axis as shown in Figure 28. The two angular momenta couple to form a total vibronic angular momentum ± K with K = | ± Λ ± |.…”
Section: Vibronic Coupling: the Renner-teller And Jahn-teller Effectsmentioning
confidence: 99%
“…] and thus particularly interesting. We refer to Section 2.3.6, Köppel et al 2011: Theory of the Jahn-Teller Effect, this handbook and also to the bibliography, for more comprehensive and exhaustive treatments of the JT effect.…”
Section: Electronic Transitions and The Jahn-teller Effectmentioning
confidence: 99%
See 1 more Smart Citation